Association Between Work Fatigue and Musculoskeletal Disorders Among Online Motorcycle Taxi Drivers: Ahmad Farid Umar, Elwindra, Debby Syahru Romadlon - Ahmad Farid Umar; Elwindra; Debby Syahru Romadlon (Jurnal Persada Husada Indonesia, 2026)
Research Objective: Online motorcycle taxi drivers are exposed to prolonged working hours and repetitive physical activities that may increase the risk of work fatigue and musculoskeletal disorders (MSDs). These conditions can negatively affect drivers’ health and productivity. Understanding the relationship between work fatigue and musculoskeletal complaints is important for developing effective occupational health interventions. This study aimed to analyze the association between work fatigue and musculoskeletal complaints among online motorcycle taxi drivers. Methodology: This study employed a quantitative analytic design with a cross-sectional approach. A total of 100 online motorcycle taxi drivers in Jakarta and Bekasi were selected using accidental sampling techniques. Work fatigue was measured using the Industrial Fatigue Research Committee (IFRC) questionnaire, while musculoskeletal complaints were assessed using the Nordic Body Map (NBM) instrument. Data were analyzed using descriptive statistics and Chi-square tests with a 95% confidence level. Results: The results showed that 44% of respondents experienced high fatigue, while 29% experienced moderate fatigue. Musculoskeletal complaints were most commonly reported in the neck (62%), lower back (58%), and waist (55%). Statistical analysis indicated a significant association between work fatigue and musculoskeletal disorders (p = 0.002). Drivers with high fatigue levels had a 4.1-times greater risk of experiencing musculoskeletal complaints compared to those with low fatigue levels (OR = 4.1; 95% CI: 1.8–9.2). Conclusion: There is a significant association between work fatigue and musculoskeletal complaints among online motorcycle taxi drivers. These findings highlight the importance of fatigue management and ergonomic awareness to reduce occupational health risks and improve drivers’ well-being.